2020
DOI: 10.1177/0361198120910743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Connected Vehicle Weather and Work Zone Warnings on Truck Drivers’ Workload and Distraction using Eye Glance Behavior

Abstract: This study acts in support of the Wyoming Department of Transport (WYDOT) connected vehicle pilot efforts in the deployment of effective, safe, and user-centered connected vehicle (CV) applications and human machine interface (HMI) displays. This study sought to quantify the workload demands and distraction introduced by the pilot’s spot weather impact warning (SWIW) and work zone warning (WZW) applications on professional truck drivers. Using driving simulator experimentation and eye-tracking technology, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Few studies have assessed the impact of in-cab alerts and messages on improving truck safety. A simulator study conducted as a part of the Wyoming DOT CV Pilot Program on sending advanced weather event and work zone notifications to commercial trucks found that the CV notifications have promising safety benefits in improving driver behavior and response times [25] [26]. The study also highlighted that the display of multiple work zone warnings may have introduced little to moderate distraction for some participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few studies have assessed the impact of in-cab alerts and messages on improving truck safety. A simulator study conducted as a part of the Wyoming DOT CV Pilot Program on sending advanced weather event and work zone notifications to commercial trucks found that the CV notifications have promising safety benefits in improving driver behavior and response times [25] [26]. The study also highlighted that the display of multiple work zone warnings may have introduced little to moderate distraction for some participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is worth mentioning that the HMI used in this study was carefully designed based on standards for effective HMIs, including readability, clarity, interpretability, accessibility, and ease of handling ( 69 ). Under the WYDOT CV pilot, the effectiveness of the designed HMI and different auditory warning modalities, as well as their minimal distraction impact on drivers, were comprehensively analyzed using vehicles’ trajectories, questionnaire survey, and eye-tracking analysis ( 40 , 47 , 70 73 ). These analyses ensured the reliability of this study’s results.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…As regards to "gender difference", some studies suggested that males showed more confidence and engaged more in distracted driving [53], while others indicated that gender difference exclusively was not significant [54]. "Professional drivers" are a group of special concern due to the long driving time and tedious task in vehicles [55][56][57]. In addition, psychological factors, including mainly "working memory capacity" [58], "executive functioning" [59], "mental workload" [28], "risk perception" [60], "attitude" [60] and "self-regulation" [61], have been extensively discussed in relation to driving distraction.…”
Section: Plos Onementioning
confidence: 99%